Fenomena Pembatalan Permohonan Paspor dalam Implementasi Kebijakan M-Paspor pada Kantor Imigrasi Tanjung Perak - Mohamad Wahyudiantoro; Edwinarta, Caesar Demas; Syarif, Rahmad (Universitas Brawijaya, 2022)
This article is a study of the phenomenon of cancellation of passport applications in the implementation of M-Paspor policy at Tanjung Perak Immigration Office. The implementation of M-Paspor policy was released in early 2022 led to the phenomenon of cancellation of passport application with many reasons. Some of the reasons for cancelling the application are because the passport applicant is not attend on the specified schedule, the applicant can’t complete the required documents that need to be attached or the mistake in applying passport application. This study uses a qualitative method with case study approach Analyzis uses public policy’s theory and consept of public policy’s implementation. The result of the study stated that the M-Passport policy requires more socialization and additional information regarding the detailed application requirements that need to be completed by the applicant in accordance with the purpose of the passport application as well as a more intensive notification feature to minimize error in submitting a passport application by the passport applicant.